Money, the market, and the military origins of the American System - Nicholas Miller Trebat (Economia e Sociedade)
Abstract This article discusses the development of mass production technology in the United States. Like spaceflight and the computer, this technology grew out of a state-led effort to promote technical progress in weapons and defense production, giving rise to what was known in the 19th century as the “American System of manufactures”. Though the roots of this system in military-industrial policy are well-established, economists continue to suggest that technical progress in 19th-century America was a market-driven affair, led by entrepreneurs eager to reduce production costs and obtain patents. We offer a different perspective, based on extensive historical research on this topic. We discuss the origins of interchangeable parts technology in Europe, its early development in the United States, and its diffusion to consumer goods manufacturing after 1850. We also reflect on the reasons for the United States War Department’s interest in this technology after 1800.